Representation in the digital age between online reputation and fake challenge - Antonelli, Carlotta (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
The proposal analyses the relationship between fake news and social media challenges. Through the content analysis of the case studies Jonathan Galindo, Momo Game and Blue Whale Challenge (Yin, 2018) the evolution of the phenomenon in the relationship between newsworthiness and fake news will be reconstructed, showing how the information system tries to "shape the public discourse" around online youth challenges, offering short-circuits between reality and imagination (Bennato, 2018).